Near-Threshold Computing and Minimum Supply Voltage of Single-Rail MCML Circuits - Ruiping Cao; Jianping Hu (Journal of Electrical and Computer Engineering)
In high-speed applications, MOS current mode logic (MCML) is a good alternative. Scaling down supply voltage of the MCML circuits can achieve low power-delay product (PDP). However, the current almost all MCML circuits are realized with dual-rail scheme, where the NMOS configuration in series limits the minimum supply voltage. In this paper, single-rail MCML (SRMCML) circuits are described, which can avoid the devices configuration in series, since their logic evaluation block can be realized by only using MOS devices in parallel. The relationship between the minimum supply voltage of the SRMCML circuits and the model parameters of MOS transistors is derived, so that the minimum supply voltage can be estimated before circuit designs. An MCML dynamic flop-flop based on SRMCML is also proposed. The optimization algorithm for near-threshold sequential circuits is presented. A near-threshold SRMCML mode-10 counter based on the optimization algorithm is verified. Scaling down the supply voltage of the SRMCML circuits is also investigated. The power dissipation, delay, and power-delay products of these circuits are carried out. The results show that the near-threshold SRMCML circuits can obtain low delay and small power-delay product.